Dynamic Voltage Stability Comparison of Thermal and Wind Power Generation with Different Static and Dynamic Load Models - Lina F. Acevedo; Gilbert Bothia-Vargas; John Edwin Candelo (Institute of Advanced Engineering and Science, 2018)
This paper presents a static and dynamic voltage stability analysis of a power network with thermal and wind generation considering static and dynamic load models. The thermal plant was modeled as a synchronous machine and the wind farm as a variable speed induction generator based on a doubly-fed induction generator. The load considered the ZIP, exponential recovery, induction motor, and frequency-dependent load models. The bifurcation points were found by continuation power flow and sensitivity analyses. In addition, dynamic voltage stability assessments were performed considering changes in the moment of inertia and the frequency parameters. All simulations were carried out in a 4-bus power system and using the power system analysis toolbox (PSAT) and MATLAB script code. The results show that the thermal generator had difficulties to maintain stability under dynamic load variations and frequency changes, the wind generator had difficulties to maintain voltage for the load with induction motors, and both generators had difficulties when the moment of inertia is increased.